Correlation Study of Self Eficacy with Learning Motivation at Students: Studi Korelasi Efikasi Diri dengan Motivasi Belajar pada Siswa - Helviana, Sania; Sudarmi; Supriyatna, Asep (Institut Pendidikan Indonesia, 2022)
Self-efficacy and learning motivation are psychological factors that important to supporting the student learning outcomes. the successful of learning is determined by the factors of efficacy and motivation. Several studies explain that the factors of self-efficacy and learning motivation are very important in supporting student learning outcomes. This study uses a quantitative approach to know the relationship between self-efficacy and student motivation in social studies learning. The sample in this study were class VIII students of SMPN 1 Cisompet. The instruments used in this study were questionnaires and documentation. Data collection techniques using validity and reliability tests. The data analysis technique used is descriptive data analysis, normality test, linearity test, regression test, correlation test with product moment, and determination test. The research results show. First, how is the self-efficacy of students at SMPN 1 Cisompet with moderate results at a percentage of 71%? Second, how are the social studies learning motivation of students at SMPN 1 Cisompet with moderate results at a percentage of 74%? Third, is there a correlation between self-efficacy and social studies learning motivation in class VIII students at SMPN 1 Cisompet with a product-moment correlation value of 0.453 greater than table 0.10? Thus, the teacher needs to pay attention that the factors of self-efficacy and student motivation influence student learning success.